Role of Resilience to Improving the Performance of Health Workers: A Systematic Review - Febrina Secsaria Handini; Kusnanto Kusnanto; Tri Johan Agus Yuswanto (Universitas STRADA Indonesia, 2020)
This systematic review is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The databases used in this study include Scopus, Science Direct, PubMed, and Pro Quest, limited to publications from 2016 to 2020 and full-text articles. The keywords used are